RELATIONSHIP BETWEEN INTERNSHIP AND ENTREPRENEURIAL SPIRIT WITH YOUTH INDEPENDENCE IN PARIS VILLAGE, GORONTALO REGENCY - Fadliyanto Ibrahim; Abdul Rahmat; Abd. Hamdi Isa; Rusmin Husain; Mohamad Zubaidi (European Journal of Humanities and Educational Advancements, 2022)
Youth is the next generation of the nation which carries the mandate to make a nation more advanced and has high competitive value at the world level. But how unfortunate it would be if a village was inhabited by many youths but so many were destroying it. This research method uses quantitative methods where the research method is a scientific procedure or method to obtain data with a specific purpose. The results of the study show that there is a relationship between work internships and independence, there is a relationship between the entrepreneurial spirit and independence and there is a simultaneous relationship between work internships and entrepreneurial spirit with youth independence.